Efficacy and mechanism of action of harmine derivative H-2-104 against Echinococcus granulosus infection in mice - Huijing Gao; Qinwei Xu; Jiang Zhu; Kadierya Kuerban; Bei Chen; Jun Zhao; Kalibixiati Aimulajiang; Liang Teng (BMC Veterinary Research)
Abstract Background Cystic echinococcosis (CE) is a chronic zoonotic parasitic disease caused by the parasite Echinococcus granulosus (E. granulosus). Currently, pharmacologic treatments are limited to albendazole and mebendazole; however, these treatments are associated with significant side effects and limited therapeutic efficacy, highlighting the urgent need for the development of new drugs. Harmine (HM) has been reported to exhibit potent antiparasitic effects, although it is also accompanied by notable neurotoxicity. H-2-104, a derivative of HM obtained through structural modification of its parent nucleus, represents a promising candidate for further investigation. This study aims to assess the in vivo and in vitro efficacy of H-2-104 against E. granulosus and to elucidate the mechanism of action of H-2-104 against CE from a metabolomics perspective. Methods In vitro pharmacodynamics experiments were conducted to assess the inhibitory activity of H-2-104 against E. granulosus protoscoleces (PSCs). Following this, a mouse model of E. granulosus infection was established to explore the inhibitory effects against E. granulosus of H-2-104 at low, medium, and high concentrations. Additionally, non-targeted metabolomic approaches were utilized to analyze the serum and liver samples from mice in the control group, model group, and H-2-104 treatment group with the aim of identifying relevant biomarkers and crucial metabolic pathways involved in the response to H-2-104 treatment. Results The in vitro results demonstrated that H-2-104 exhibited significantly superior inhibitory activity against PSCs compared to harmine and albendazole. Morphological observations revealed marked alterations in the ultrastructural characteristics of PSCs treated with H-2-104. In vivo pharmacodynamic studies showed that H-2-104 at a dosage of 100 mg/kg exhibited the highest cyst inhibition rate, which was (73.60 ± 4.71)%. Metabolomics analysis revealed that 64 serum metabolites were significantly altered, primarily involving metabolic pathways such as necroptosis, linoleic acid metabolism, and phenylalanine metabolism. Additionally, 81 liver metabolites were identified with significant differences, mainly involving metabolic pathways like fructose and mannose metabolism, and glycerophospholipid metabolism. Conclusions H-2-104 exhibits significant activity both in vitro and in vivo, suggesting its potential as a promising new drug for the treatment of CE. The anti-CE effects of H-2-104 may be attributed to its regulation of multiple biological pathways, including cell apoptosis, amino acid metabolism, and glucose metabolism.